Epidemiological, clinical, and pathologic characteristics of lymphoma cases in Cayetano Heredia National Hospital from 1998 to 2008 - Padilla Valdez, Juan José (2011)
Objective: To determine the epidemiological, clinical and pathological characteristics of lymphoma cases in Cayetano Heredia National Hospital. Material and methods: We conducted a descriptive and retrospective case series including 433 patients with lymphoma diagnosed from 1998 to 2008. Results: Average age of patients was 44.8 years, and 60.04% were male. Most frequent birthplace and living area was Lima, with 61.5% and 90% of all patients, respectively. Most frequent symptoms were weight loss and lymph node enlargement (40.5% and 3,7%, respectively). More than half of all patients (55.08%) were in I-II clinical stages. The most frequent location of the disease was in the lymph nodes (55.1%). Extranodal locations were the gastrointestinal tract (15.2%) and the skin (10.8%). The B immunophenotype corresponded to 57.8% o all non-Hodgkin lymphoma cases, and the most common histological type was diffuse large cell lymphoma (35.8%), and Hodgkins disease accounted for 14.08%. Of all treated patients, 78.12% had complete and partial response. Therapy for Hodgkins disease was ABVD, with 90.97% of all patients achieving complete and/or partial response. Only 23.45% of all patients were reported as dead. Conclusions: Lymphoma patients seen in Cayetano Heredia National Hospital have similar characteristics compared to was is reported in a worldwide basis.